Population Aging and Global Capital Flows in a Parallel Universe - Brooks, Robin (IMF Working Papers; Working Paper, 2000)
This paper explores the global impact of population aging, using a calibrated overlapping generations model of eight world regions to simulate the effects of historical and projected demographic trends on international capital flows. The simulations show that there will be a turning point in regional savings - investment balances between 2010 and 2030 when the European Union and North America will experience a substantial decline in savings relative to investment as their populations age rapidly. This shift will be financed by capital flows from less developed regions which are projected to become capital exporters.